Anishinaabeg Women's Wellbeing: Decolonization through Physical Activity - Mcguire-Adams, Tricia (Université d'Ottawa / University of Ottawa, 2018)
Settler colonialism has detrimental effects on the health and wellbeing of Indigenous peoples, as seen, for example, in the disproportionately high rates of chronic diseases experienced among Indigenous peoples. Indigenous peoples in Canada experience higher levels of ill health related to obesity, diabetes, and other chronic conditions than non-Indigenous people. Indigenous women experience greater incidents of chronic disease than men and are thus particularly vulnerable to ill health. Current research has focussed on documenting the health disparities between Indigenous and non-Indigenous peoples. While insightful, health disparity research reproduces settler colonial discourses of erasure and provides no meaningful or lasting solutions for addressing these disparities, thus demonstrating the need for Indigenous-led thinking regarding potential solutions. Therefore, the guiding research question for my dissertation was, “Can physical activity that encompasses a decolonization approach be a catalyst for regenerative wellbeing for Anishinaabeg women?” Using Indigenous feminist theory that is informed by Anishinaabeg gikendaasowin, I looked to the dibaajimowinan of Anishinaabeg women, Elders, and urban Indigenous women, which occurred in three stages of research and culminated in five publishable papers. In the first stage of research, I interviewed seven Anishinaabekweg who are exemplars of decolonized physical activity. In the second stage of research, I held a sharing circle with eight Elders from Naicatchewenin in Treaty #3 territory. In the last stage of research, I implemented Wiisokotaatiwin with 12 urban Indigenous women with the Odawa Native Friendship Centre, my community partner. The results of my research revealed that wellbeing for Indigenous women can be improved through decolonized physical activity, remembering Anishinaabeg stories, and building community in urban spaces. More specifically, these activities are important resistance tools that can lead to meaningful ways of addressing embodied settler colonialism and can also make strong contributions to Indigenous health research. Overall, my research showcased how Anishinaabeg gikendaasowin can be used as a foundation to improve Indigenous women’s health and wellbeing.